Reforming the Gender-Related Index (GDI) and the Gender Empowerment Measure (GEM): Some specific proposals - Stephan Klasen; Dana Schüler (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2009)
In 2005 and 2006, the Human Development Report Office undertook a review of UNDP's gender-related indicators, particularly the Gender-Related Development Index (GDI) and the Gender Empowerment Measure (GEM). Background papers as well as the results of the process were published in 2006 (e.g. Klasen 2006a), and summarized in the Human Development Report 2006. Here we extend this work by adjusting and extending some of the recommendations made there, by making concrete proposals for the two gender-related indicators and by presenting illustrative results for these proposed measures. The most important proposals include the calculation of a male and female HDI, as well as a gender gap index GGI to replace the GDI, that can be interpreted more directly as a measure of gender inequality. Regarding the GEM, the most important changes are different ways to deal with the earned income component and also to replace it with a more straight-forward procedure to calculate the measure. As shown below, the ranking of countries are very different for the new measures proposed here, compared to the current GDI and GEM.
Keywords: I31; J16; 330; Gender inequality measures; GDI; GEM; UNDP; Entwicklungsindikator; Geschlecht; Geschlechterdiskriminierung; Frauenpolitik; Welt